Odpowiedź :
Obliczenia
[tex]1\% \ z \ 10^{11}=10^{11}:100=10^{11}:10^2=10^{11-2}=10^9\\\\10\% \ z \ 10^9=10^9:10=10^{9-1}=10^8\\\\50\% \ z \ 2^7=2^7:2=2^{7-1}=2^6\\\\25\% \ z \ 2^{33}=2^{33}:4=2^{33}:2^2=2^{33-2}=2^{31}[/tex]
[tex]a) \ 1\% \ liczby \ 10^{11} = \frac{1}{100}\cdot10^{11} = \frac{1}{10^{2}}\cdot10^{11} = 10^{-2}\cdot10^{11} = 10^{-2+11} = 10^{9}\\\\b) \ 10\% \ liczby \ 10^{9} = \frac{10}{100}\cdot10^{9} = \frac{1}{10}\cdot10^{9} = 10^{-1}\cdot10^{9} = 10^{-1+9} = 10^{8}\\\\c) \ 50\% \ liczby \ 2^{7} = \frac{50}{100}\cdot2^{7} = \frac{1}{2}\cdot2^{7} = 2^{-1}\cdot2^{7} = 2^{-1+7} = 2^{6}[/tex]
[tex]d) \ 25\% \ liczby \ 2^{33} =\frac{25}{100}\cdot2^{33} = \frac{1}{4}\cdot2^{33} = \frac{1}{2^{2}}\cdot2^{33} = 2^{-2}\cdot2^{33} = 2^{-2+33} = 2^{31}[/tex]
Wyjaśnienie:
[tex]1\% = \frac{1}{100}\\\\a^{m}\cdot a^{n} = a^{m+n}\\\\a^{-n} = (\frac{1}{a})^{n} \ \ dla \ n\neq 0[/tex]